Propuesta de un modelo de densificación de los lotes vacíos en los barrios consolidados del sector norte de la ciudad de Loja - Maldonado Quito, Diego Ricardo (2018)
Abstract:The anarchic growth of the city due to real estate and political interests on the need for housing, brings with it a series of empty spaces that are an integral part of the city. These gaps generate deterioration of the landscape, lending to inappropriate uses, affecting the health and safety of its inhabitants. The main objective of this research was to propose a densification model in the northern sector of the city of Loja, in a neighborhood in the process of consolidation, Barrio Las Pitas I, by using empty lots. The proposed methodology is based on, review of bibliography, study of international and local regulations, conducting surveys and inventory of lots through computer systems, identifying and classifying, studying the appropriate areas and how they should be intervened. As a result, the densification proposal would make the neighborhood more compact and equitable by intensifying the more efficient use of the land, determined by the existing infrastructure and the improvement of it, added to the equipment and transport systems will make it possible to satisfy the housing needs.